Prinsip-Prinsip dan Efektivitas Desentralisasi Pendidikan Dalam Rangka Meningkatkan Mutu dan Relevansi Pendidikan - Subijanto – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The effectiveness of decentralization is not only giving involving authority process and budgetfrom central government to local government but also giving authority as a whole to the school throughholistic authority in defining policy of education, such as: teaching-learning process organization,management of teacher, structur and school planning, and school budget resources. The Act number 20of the year 2003 about National Education System was support the authority education budget directly toevery school through school based management. The quality and relevance of education in each stage ofeducation had been stated. Therefore, the Government was commited to invest for education as asolution of nation in the future that is through 20 % Fiscal National Budget for education could beoperationalized excluded government education dan salary of teacher. For empowering supportdevelopment of education the government shoud be collaboration with local government, society, andprivate company in conducting the quality of education. To increase the nation of competitiveness, thequality of education which is equal to the international standard need to be developed, to be monitor, andto be evaluate stages by stages and continuously in every region with more emphasises on relevancybased on demand, the characteristic of local region and prominence to local content based education.Â ABSTRAKDesentralisasi pendidikan yang efektif tidak hanya melibatkan proses pemberian kewenangandan pendanaan yang lebih besar dari Pemerintah Pusat ke pemerintah daerah, tetapi desentralisasiharus menyentuh pemberian kewenangan yang lebih besar ke sekolah dalam menentukan berbagaikebijakan, seperti organisasi dan proses belajar-mengajar, manajemen guru, struktur dan perencanaandi tingkat sekolah, dan sumber pendanaan sekolah. Undang-Undang Nomor 20/2003 tentang Sisdiknasmendukung dengan memberikan kewenangan otonomi pendidikan langsung kepada setiap satuanpendidikan melalui manajemen berbasis sekolah. Mutu dan relevansi pendidikan ada pada setiap prosespentahapan pada satuan pendidikan. Komitmen Pemerintah untuk berinvestasi pada pendidikan sebagaisolusi masa depan bangsa harus segera diwujudkan melalui pengalokasian 20% APBN untuk pendidikandi luar anggaran pendidikan kedinasan dan gaji guru. Untuk memperkuat dukungan pengembanganpendidikan, diperlukan kemitraan yang erat antara pemerintah, pemerintah daerah, dan masyarakatdalam menyelenggarakan pendidikan yang bermutu. Untuk meningkatkan daya saing bangsa, pendidikanunggulan bertaraf internasional perlu dikembangkan, dimonitor, dan dievaluasi secara bertahap danberkesinambungan di setiap daerah dengan menekankan relevansi dengan kebutuhan, ciri khas daerah/keunggulan lokal.